Developing a religious program for breast cancer survivors - Alwi, Khadijah; Ahmad, Farizah; Amadhila, Helena Naitsuwe (2007)
The purpose of this study was to discover and uncover the nature of planning and learning from an adult religious education program designed for KanWork, a support group for women breast cancer survivors.A qualitative research design was used in order to arrive at a better understanding of the personal meaning and experience of program planning from the adult educator's view and learning from the participants' view. Using purposive sampling,the adult educator and four participants, were selected and interviewed.The findings were classified into several themes: interests affect planning; perceived role affects educational mission, negotiating about needs, connecting with the learners and evaluation and accountability. This study indicated that understanding program development for adult learners is essential in developing effective adult educational programs. Although there are external factors those impact adult education, the religious educator's background characteristics, beliefs and values can impact planning and design of adult education programs.